Real Fingerprint Detection System (RFDS) Based on Image Quality Measures and Six Classifiers - Mriheel, Abdurahman Ibrahim (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Fingerprint detection in biometrics is an important field of study in our new modern world, many forensic departments around the world use fingerprints as the key to detect criminals and bring them justice. To improve the accuracy of fingerprint detection system we implemented a Real Fingerprint Detection System (RFDS) that has high performance level of detecting real and fake fingerprint images. In this thesis, we present an RFDS system based on image quality measures (IQM’s) to detect real fingerprint images and fake fingerprint images. We performed different RFDS experiments with 25, 10, 15, and 5 IQM’s; they showed sufficient quality of real and fake fingerprint images detection. We compared our RFDS using 25, 15, 10, and 5 IQM’s with RFDS that has used 25 IQMs. Based on the comparison in this thesis we can conclude that the best result from all these RFDS is the one with 25 IQMs, because it’s HTER score is the minimum one with 0.3%, and the worst RFDS is the one with the 15 IQMs which has the maximum HTER score with 14.8%. Keywords: Biometrics, Image Quality Measure, Real and Fake Fingerprint Image, Classifier.

ÖZ: Biyometride parmak izi tespiti, yeni modern dünyamızda önemli bir çalışma alanıdır, dünyadaki birçok adli departman, suçluları tespit etmek ve adalet getirmek için parmak izi kullanmaktadır. Parmak izi algılama sisteminin doğruluğunu artırmak için, gerçek ve sahte parmak izi görüntülerini algılamada yüksek performans seviyesine sahip bir Gerçek Parmak İzi Algılama sistemi (RFDS) uyguladık. Bu tezde, gerçek parmak izi görüntülerini ve sahte parmak izi görüntülerini tespit etmek için görüntü kalitesi ölçümlerine (IQM'ler) dayanan bir RFDS sistemi sunuyoruz. 25, 15, 10 ve 5 IQM'lerle farklı RFDS deneyleri gerçekleştirdik; yeterli kalitede gerçek ve sahte parmak izi görüntüleri algılama özelliği gösterdiler. 25, 15, 10 ve 5 IQM kullanarak RFDS'imizi 25 IQM kullanan RFDS ile karşılaştırdık. Bu tezdeki karşılaştırmaya dayanarak, tüm bu RFDS'lerden en iyi sonucun 25 IQM'ye sahip olduğu sonucuna varabiliriz, çünkü HTER puanı % 0.3 ile en düşük olanıdır ve en kötü RFDS ise %14.8 HTER puanı ile 15 IQM'ye sahip olanıdır. Anahtar Kelimeler: Biyometri, Görüntü Kalitesi Ölçüsü, Gerçek Ve Sahte Parmak Izi Görüntüsü, Sınıflandırıcı.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2020. Supervisor: Assoc. Prof. Dr. Alexander Chefranov.
Keywords: Computer Engineering; Computer Vision; Image Processing; Biometrics; Image Quality Measure; Real and Fake Fingerprint Image; Classifier